Immunoregulatory role of exosomal circRNAs in the tumor microenvironment - Lv, Cunming; Chen, Jinhao; Wang, Yuxiang; Lin, Yichen (Frontiers in Oncology, 2025)
As cancer incidence and mortality rates rise, there is an urgent need to develop effective immunotherapy strategies. Circular RNA (circRNA), a newly identified type of non-coding RNA, is abundant within cells and can be released via exosomes, facilitating communication between cells. Studies have demonstrated that exosomal circRNAs can alter the tumor microenvironment and modulate immune responses by influencing the functions of T cells, natural killer (NK) cells, and macrophages, thereby enabling tumors to evade the immune system. Moreover, exosomal circRNAs show potential as diagnostic biomarkers and therapeutic targets for cancer. This review summarizes the regulatory roles of exosomal circRNAs in immune cells and their potential applications in cancer progression and treatment, highlighting their promise in improving cancer immunotherapy. Future research should concentrate on understanding the mechanisms of key exosomal circRNAs and developing targeted immunotherapy methods.